Association of polymorphisms in the vitamin D receptor gene with susceptibility to and severity of hand, foot, and mouth disease caused by coxsackievirus A16. Issue 3 (2nd December 2019) - Li, Ya‐Ping; Wang, Mu‐Qi; Deng, Hui‐Ling; Li, Mei; Zhang, Xin; Dang, Shuang‐Suo; Zhai, Song
Abstract: Coxsackievirus A16 (CA16) remains the most common causative agent of hand, foot, and mouth disease (HFMD), and is related to high incidence and critical complications. Vitamin D receptor (VDR) activity might affect the outcome of CA16 infection. Our case‐control research aims to evaluate the relationship between VDR polymorphisms in the gene encoding and susceptibility to and severity of HFMD due to CA16. Three single‐nucleotide polymorphisms (SNPs) of VDR gene were selected according to functional prediction and linkage disequilibrium, and were examined utilizing the SNPscan method to identify possible associations with HFMD caused by CA16. A significant relationship was found in the HFMD cases of polymorphism rs11574129 (GA vs GG: odds ratio (OR) = 0.068, 95% confidence interval (CI) = 0.007‐0.693, P  = .023; GA + AA vs GG: OR = 0.322, 95%CI = 0.106‐0.984, P  = .047), and vitamin D levels in genotype AA were significantly higher than those in genotype GG ( P  < .05). These results suggest that VDR rs11574129 may influence genetic susceptibility to CA16‐associated HFMD.